RESEARCH OF THE COMBUSTION PROCESS OF LIQUID FUELS AT THE CHANGE OF THE INJECTED PARTICLE’S VELOCITY - Askarova, A.S.; Voloshina, I.E.; Ryspayeva, M.Zh.; Nevskii, E.S. (Recent Contributions to Physics, 2021)
The combustion process of liquid fuel in the combustion chamber on the basis of the solution for differential two-dimensional equations of the turbulent reactive flows has been numerically researched. The influence of the spray velocity on the combustion of liquid fuel has been studied.